The Politicization of Women’s Rights in Malaysia: The Drive Behind the Impasse of Fatwa Obligating Female Circumcision - Nabilah Nur Abiyanti (Institute of International Studies, 2019)
Under the new premiership of Najib Razak in 2009, a fatwa obligating female circumcision for all Muslim women in Malaysia was issued. It was issued following the 2008 “Political Tsunami” despite the heightened promotion of global zero tolerance towards the practice. The dilemma between adhering to Malaysia’s obligation under CEDAW and CRC and the need to regain control amidst domestic political upheaval has led the fatwa to be left on impasse, until date. Thus, this article aims to find the reason behind the Malaysian government’s decision to leave the fatwa on the impasse focusing on two stages of public policy analysis. The analysis of cost and benefit in the policy formulation stage has resulted in equal cost and benefit to each policy option –to accept or reject the fatwa. The result of the equal cost and benefit analysis is also due to the variety of actors in the decision-making process with different positions, interests and bargaining positions. From using a rational model of the decision-making process, the reason why the Malaysian government leaves the fatwa on impasse was driven by the Malaysian goal under Najib Razak, which required not only domestic stability but also vast international support.